2007
DOI: 10.1016/j.ejheart.2007.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cardiac resynchronisation therapy on different types of sleep disordered breathing

Abstract: Aims: This study investigates the influence of cardiac resynchronisation therapy (CRT) on sleep disordered breathing (SDB) in patients with severe heart failure (HF). Methods and results: Seventy-seven patients with HF (19 females; 62.6 ± 10 years) eligible for CRT were screened for presence, type, and severity of SDB before and after CRT initiation (5.3 ± 3 months) using cardiorespiratory polygraphy. NYHA class, frequency of nycturia, cardiopulmonary exercise, 6-minute walking test results, and echocardiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 38 publications
5
57
0
9
Order By: Relevance
“…[30][31][32][33][34][35] The present study included 12 patients at least 12 months after CRT implantation, and CSR-CSA and depressed cardiac function still remained in spite of standard pharmacotherapy and CRT in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33][34][35] The present study included 12 patients at least 12 months after CRT implantation, and CSR-CSA and depressed cardiac function still remained in spite of standard pharmacotherapy and CRT in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Gabor et al observed no change in blood O 2 saturation despite a clear alleviation of CSA by CRT, 10 while Oldenburg et al noted a mitigation of O 2 desaturation. 11 The duration of pulse oximeter O 2 saturation < 90% during BUV40 was significantly longer among our patients with history of HF decompensation than our patients without ( Table 3), suggesting that patients with previous cardiac decompensation were more hypoxic at baseline than patients who never previously suffered an episode of acute HF. This did not seem strictly related to SA, since AHI was not highest among patients with the longest duration of pulse oximeter O 2 saturation < 90%.…”
Section: Discussionmentioning
confidence: 65%
“…Measurements of BNP have not been included in the majority of studies of CRT and sleep disordered breathing. [9][10][11][12]14 Lüthje et al observed a decrease in BNP after 3 months of CRT, of similar amplitude in patients with versus without CSA. 13 In that study, BNP was unchanged by overnight overdrive atrial pacing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations